Pengembangan Motorik Kasar Anak melalui Permainan Tradisional "Tarik Upih" Berbasis Kearifan Lokal - Wahyuni, Ida Windi; Muazimah, Ajriah; Misdah, . (Jurnal Pendidikan Anak Usia Dini Undiksha, 2020)
A traditional game of tarik upih for children is a fun game. Tarik upih is the stem or "base" of the areca nut leaf. Tarik upih can be played by two or more people. Through traditional play-ups, children are taught to be honest, cooperate, tolerance, tough, and train children's psychomotor movements. The purpose of this study is to determine the development of children's gross motor skills through traditional play-based traditional wisdom. This qualitative study used 15 research subjects of PAUD Harapan Bunda Kelurahan Sungai Pagar Kecamatan Kampar Kiri Hilir Kecamatan Kampar conducted in January 2020. The results showed that students had achieved Very Good Developing (BSB) results in coordinating movements for flexibility, balance (73%), coordinating eye-foot-hand-head-head movements (86.7%), and doing a physical play with rules (80%). Traditional play games for kids are taught to be honest, cooperate, tolerance, tough, train children's psychomotor movements, form a caring person, and have a love for their culture. The conclusion is the development of gross motor skills through tarik upih of traditional play based on local wisdom developed very well in PAUD Harapan Bunda students in Sungai Pagar Village, Kampar Kiri Hilir District, Kampar Regency. Keywords: Education, Children, Local Wisdom, Traditional Games, Pull-Out Activity